Critical Appraisal of Emergency Medicine Education Research: The Best Publications of 2013. (November 2014) - Farrell, Susan E.; Kuhn, Gloria J.; Coates, Wendy C.; Shayne, Phillip H.; Fisher, Jonathan; Maggio, Lauren A.; Lin, Michelle; Burton, John
Abstract Objectives The objective was to critically appraise and highlight methodologically superior medical education research articles published in 2013 whose outcomes are pertinent to teaching and education in emergency medicine (EM). Methods A search of the English‐language literature in 2013 querying Education Resources Information Center (ERIC), PsychINFO, PubMed, and Scopus identified 251 EM‐related studies using hypothesis‐testing or observational investigations of educational interventions. Two reviewers independently screened all of the publications and removed articles using established exclusion criteria. Six reviewers then independently scored the remaining 43 publications using either a qualitative a or quantitative scoring system, based on the research methodology of each article. Each scoring system consisted of nine criteria. Selected criteria were based on accepted educational review literature and chosen a priori. Both scoring systems used parallel scoring metrics and have been used previously within this annual review. Results Forty‐three medical education research papers (37 quantitative and six qualitative studies) met the a priori criteria for inclusion and were reviewed. Six quantitative and one qualitative study were scored and ranked most highly by the reviewers as exemplary and are summarized in this article. Conclusions This annual critical appraisal article aims to promote superior research in EM‐related education, by reviewing and highlighting seven of 43 major education research studies, meeting a priori criteria, and published in 2013. Common methodologic pitfalls in the 2013 papers are noted, and current trends in medical education research in EM are discussed.